Sebuah studi literatur mengenai pengukuran kinerja rantai pasok pada industri strategis di Indonesia - Joko Sulistio (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
Article 33 in 1945 Constitution of the Republic of Indonesia is the essence of strategic industry operative. Consistent with supply chain management (SCM), the objective is to fulfil costumer value. Therefore, SCM performance measurement become significant. The current measurement was not developed from the article 33. This research objectives are to study the current measurement framework and to discover research gap to develop measurement framework suitable for strategic industry in Indonesia. The method used in this research is systematic literature review. This study found that there is no performance measurement that developed upon article 33. Further performance measurement development is crucial to accommodate article 33 and grounded theory is promising for such work.